Effectiveness of Inositol Supplementation in Improving Ovulation Rates in PCOS - Sajida, Bibi; Batool, Memoona; Punshi, Monica; Juriasinghani, Manesha; Inayat, Afifa; Gulab, Nargis; Depa, Ramsha (Journal of Neonatal Surgery, 2025)
Background: To evaluate the effectiveness of myo-inositol supplementation in enhancing ovulation rates and restoring menstrual regularity in women diagnosed with PCOS. Methods: A prospective interventional study was conducted on 72 women with PCOS from July 2023 to September 2024. Participants received myo-inositol (2000 mg twice daily) with folic acid for 12 weeks. Baseline and post-treatment clinical, biochemical, and ultrasound parameters were recorded. Ovulation was confirmed through mid-luteal progesterone levels or ultrasound follicle monitoring. Pre- and post-treatment data were analyzed using paired t-tests and chi-square tests. Results: Following inositol supplementation, 58.3% of participants achieved ovulation, and 65.3% reported regular menstrual cycles. There was a significant reduction in LH/FSH ratio and serum testosterone levels (p < 0.001). The therapy was well tolerated, with no major side effects reported. Conclusion: Myo-inositol supplementation significantly improved ovulation and hormonal profiles in women with PCOS. It may serve as an effective and safe alternative for ovulation induction, particularly in those seeking non-hormonal treatment options.